Contractile effect of Hydroalcoholic extract of Sida cordifolia L. leaves in rat aorta - Santos, Marcio Roberto Viana; Moreira, Í. J. A.; Filho, J. M. B.; Medeiros, I. A. (Scientia Plena, 2014)
In the present work, the contractile effect induced by aqueous fraction of the hydroalcoholic extract of the leaves of Sida cordifolia L. (AFSC) was investigated in the rat aorta. In the presence of functional endothelium, AFSC produced contractions in a concentration-dependent manner (EC50 = 1.23 ± 0.09 mg/mL; n=6). In the absence of functional endothelium or in the presence of L-NAME (100 <span style="font-size: 10.0pt; font-family: Symbol; mso-ascii-font-family: "Times New Roman"; mso-hansi-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-char-type: symbol; mso-symbol-font-family: Symbol; font-weight: normal; mso-bidi-font-weight: bold;" lang="EN-US">mM), the concentration-response curves to AFSC were significantly shifted to the left (EC50 = 0.84 ± 0.1 and 0.54 ± 0.15 mg/mL, respectively; n=6) with an increase of its maximal contractile response. In the presence of indomethacin (10 <span style="font-size: 10.0pt; font-family: Symbol; mso-ascii-font-family: "Times New Roman"; mso-hansi-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-char-type: symbol; mso-symbol-font-family: Symbol; font-weight: normal; mso-bidi-font-weight: bold;" lang="EN-US">mM), the concentration-response curve produced by AFSC was not changed (EC50 = 1.28 ± 0.05 mg/mL; n=6). In addition, concentration-response curves to AFSC were significantly shifted to the right in the presence of 1 <span style="font-size: 10.0pt; font-family: Symbol; mso-ascii-font-family: "Times New Roman"; mso-hansi-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-char-type: symbol; mso-symbol-font-family: Symbol; font-weight: normal; mso-bidi-font-weight: bold;" lang="EN-US">mM of prazosin (EC50 = 1.40 ± 0.01 mg/mL; n=7), but were not changed after 3 <span style="font-size: 10.0pt; font-family: Symbol; mso-ascii-font-family: "Times New Roman"; mso-hansi-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-char-type: symbol; mso-symbol-font-family: Symbol; font-weight: normal; mso-bidi-font-weight: bold;" lang="EN-US">mM of yohimbine (EC50 = 1.22 ± 0.06 mg/mL; n=6). In conclusions, these results demonstrate that the contractions induced by AFSC in the rat aorta seem to be due to an activation of <span style="font-size: 10.0pt; font-family: Symbol; mso-ascii-font-family: "Times New Roman"; mso-hansi-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-char-type: symbol; mso-symbol-font-family: Symbol; font-weight: normal; mso-bidi-font-weight: bold;" lang="EN-US">a1‑adrenergic receptors, and these seem to be negatively modulated by endothelium and release of NO.